Perspectives on election five views - Cottrell, Jack W.; Pinnock, Clark H. 1937-; Reymond, Robert L.; Talbott, Thomas B.; Ware, Bruce A.; Brand, Chad Owen (Nashvill, TN Broadman and Holman Academic, 2006)
Includes bibliographical references and index
Keywords: Election (theology)